2022
DOI: 10.3389/fphar.2022.856104
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Roles of Non-Coding RNAs in Childhood Asthma

Abstract: Asthma is a chronic airway inflammatory disease in children characterized by airway inflammation, airway hyperresponsiveness and airway remodeling. Childhood asthma is usually associated with allergy and atopy, unlike adult asthma, which is commonly associated with obesity, smoking, etc. The pathogenesis and diagnosis of childhood asthma also remains more challenging than adult asthma, such as many diseases showing similar symptoms may coexist and be confused with asthma. In terms of the treatment, although mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 159 publications
(171 reference statements)
0
6
0
Order By: Relevance
“…Asthma is a heterogenous disease comprising different phenotypes and endotypes 20,21 . Based on endotypes, T‐helper(Th)‐2‐high, Th2‐low and the mixed endotypes are described for severe asthma 22,23 . Th2‐high asthma termed as eosinophilic asthma is associated with innate and adaptive immunity, while Th2‐low asthma associated with non‐eosinophilic asthma is characterized by neutrophilic inflammation or paucicellular inflammation 24,25 .…”
Section: The Immunopathogenesis Of Asthmamentioning
confidence: 99%
See 1 more Smart Citation
“…Asthma is a heterogenous disease comprising different phenotypes and endotypes 20,21 . Based on endotypes, T‐helper(Th)‐2‐high, Th2‐low and the mixed endotypes are described for severe asthma 22,23 . Th2‐high asthma termed as eosinophilic asthma is associated with innate and adaptive immunity, while Th2‐low asthma associated with non‐eosinophilic asthma is characterized by neutrophilic inflammation or paucicellular inflammation 24,25 .…”
Section: The Immunopathogenesis Of Asthmamentioning
confidence: 99%
“… 20 , 21 Based on endotypes, T‐helper(Th)‐2‐high, Th2‐low and the mixed endotypes are described for severe asthma. 22 , 23 Th2‐high asthma termed as eosinophilic asthma is associated with innate and adaptive immunity, while Th2‐low asthma associated with non‐eosinophilic asthma is characterized by neutrophilic inflammation or paucicellular inflammation. 24 , 25 Studies have confirmed that innate immunity involving macrophages, neutrophils, mast cells and type II innate lymphoid cells (ILC2s) produce a variety of Th2 cytokines, such as interleukin (IL)‐4, IL‐5 and IL‐13, to control the persistence of allergic inflammation.…”
Section: The Immunopathogenesis Of Asthmamentioning
confidence: 99%
“…Asthma is a group of chronic inflammatory diseases ( 99 , 100 ) characterized by episodes of obstructed airflow and high airway sensitivity. It impacts the quality of life of patients by affecting lung development, and it may also represent a life-threatening condition ( 101 ). Although a number of factors may exacerbate the risk of asthma (such as exposure to air pollutants and dust-mite allergen), identifying a single direct cause is difficult ( 69 ).…”
Section: Micrornas In Bronchial Asthmamentioning
confidence: 99%
“…In addition, microRNAs are potential therapeutic targets for asthma ( 101 ). Studies have demonstrated that microRNA inhibitors or synthetic microRNA oligonucleotides can be used to inhibit upregulated microRNAs (for example, microRNA inhibitors or synthetic microRNA oligonucleotides can be used to suppress microRNA-21, -106a, -126, -145, -155 and -221 to control aberrant cytokine expression and inflammation), and that increasing tissue-specific microRNA expression using microRNA inducers may be an alternative therapeutic strategy for asthma ( 112 , 113 ).…”
Section: Micrornas In Bronchial Asthmamentioning
confidence: 99%
“…MiRNAs may participate in the process of airway remodeling, leading to airway obstruction and affecting airway function parameters. MiRNAs involved in a number of pathophysiological processes affect smooth muscle cells, the epithelium, and goblet cells and intensify the inflammatory process, causing narrowing of the bronchial lumen [ 34 ].…”
Section: Asthma Exacerbation and Mirnasmentioning
confidence: 99%